PENGARUH KUALITAS PELAYANAN TERMINAL TERHADAP KEPUASAN PENGGUNA JASA PADA MASA PANDEMI COVID-19 DI BANDARA INTERNASIONAL RADIN INTEN II LAMPUNG - Esa Trinenda Dewabuana; Anton Budiarto; Fatmawati (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This study aims to know the effect of terminal service quality on service users satisfaction at Radin Inten II Internasional Airport in Lampung during the Covid- 19 pandemic. The research method in this research is using quantitative descriptive research. The population in this study were all airline passengers operating at Radin Inten II Airport in Lampung. The sampling method in this study uses a non-probability sampling technique using quota sampling, which is a technique to determine a sample from a population that has certain characteristics used by researchers. Then the sample size used in this study were 175 respondents who were airline passengers operating at Radin Inten II Airport in Lampung. The data analysis method used in this research is SEM-PLS analysis with the help of the SmartPLS 3.3.3 program. The results showed that the terminal service quality variable (X) had a significant effect on service user satisfaction (Y) of 40.945 > 1.96 with a positive relationship of 0.863.